Modulating the Oxytocin System During the Perinatal Period: A New Strategy for Neuroprotection of the Immature Brain? - Zinni, Manuela; Colella, Marina; Batista Novais, Aline Rideau; Baud, Olivier; Mairesse, Jérôme (Frontiers in Neurology, 2018)
Oxytocin is a neurohypophysal hormone known for its activity during labor and its role in lactation. However, the function of oxytocin goes far beyond the peripheral regulation of reproduction, and the central effects of oxytocin have been extensively investigated since it has been recognized to influence the learning and memory processes. Oxytocin also has prominent effects on social behavior, anxiety and autism. Interaction between glucocorticoids, oxytocin and maternal behavior may have long-term effects on the developmental program of the developing brain subjected to adverse events during pre and perinatal periods. Oxytocin treatment in humans improves many aspects of social cognition and behavior. Its effects on the hypothalamic-pituitary-adrenal axis and inflammation appear to be of interest in neonates because these properties may confer benefits when the perinatal brain has been subjected to injury. Indeed, early life inflammation and abnormal adrenal response to stress have been associated to abnormal white matter development. Recent investigations demonstrated that oxytocin is involved in the modulation of microglial reactivity in the developing brain. This review recapitulates state-of-the art data supporting the hypothesis that the oxytocin system could be considered as an innovative candidate for neuroprotection, especially in the immature brain.